2020
DOI: 10.1108/bjm-07-2020-0236
|View full text |Cite
|
Sign up to set email alerts
|

Who benefits from time-spatial job crafting? The role of boundary characteristics in the relationship between time-spatial job crafting, engagement and performance

Abstract: PurposeUsing the theoretical framework of job demands-resources and boundary management, the purpose of this paper is to explore the moderating role of work and life boundary characteristics in the relationship between time-spatial job crafting, work engagement and job performance.Design/methodology/approachA total of 176 employees working in the IT sector and having an opportunity to use flexible work arrangements were surveyed online.FindingsWork and life boundary characteristics were found to moderate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…One example that can be provided is the causal relationship between work engagement and job crafting. Research showed two antithetical effects-namely, that work engagement promotes job crafting (Bai et al, 2021;Bajaba et al, 2021;Oprea et al, 2022;Tan et al, 2020), as well as the reversed causality for these variables (Bakker and Oerlemans, 2019;Lazauskaite-Zabielske et al, 2021;Letona-Ibañez et al, 2021;Radstaak and Hennes, 2017). The bidirectional relationship between these variables is confirmed by analyses which aggregate the previous research (Dash and Vohra, 2020;Zhang and Parker, 2019).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…One example that can be provided is the causal relationship between work engagement and job crafting. Research showed two antithetical effects-namely, that work engagement promotes job crafting (Bai et al, 2021;Bajaba et al, 2021;Oprea et al, 2022;Tan et al, 2020), as well as the reversed causality for these variables (Bakker and Oerlemans, 2019;Lazauskaite-Zabielske et al, 2021;Letona-Ibañez et al, 2021;Radstaak and Hennes, 2017). The bidirectional relationship between these variables is confirmed by analyses which aggregate the previous research (Dash and Vohra, 2020;Zhang and Parker, 2019).…”
Section: Introductionmentioning
confidence: 57%
“…, 2022; Tan et al. , 2020), as well as the reversed causality for these variables (Bakker and Oerlemans, 2019; Lazauskaite-Zabielske et al. , 2021; Letona-Ibañez et al.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential that future research implements a rigorous validating process where the content of this construct is assessed in relation to other approach types of job crafting and expected consequences. However, the intention to report these preliminary findings related to increasing workplace resources concurs with Lazauskaite-Zabielske et al (2021) and Roskams and Haynes (2019) and raises the importance of considering the working environment as an essential part of work. In new ways of working, extended work environments provide employees with flexibility (Meyer et al, 2021) and motivational profit (Ryan and Deci, 2020), but may also cause drawbacks.…”
Section: Discussionmentioning
confidence: 80%
“…Our other theoretical contribution is to stimulate the debate on the need to expand the target of job crafting to cover the operational environment of work. Evidence (Lazauskaite-Zabielske et al, 2021;Wessels et al, 2019) supports the idea of including features of new ways of working, such as time and spatial dimensions of work, as targets for employee-driven job crafting. Aligned with such suggestions, Roskams and Haynes (2019) presented the concept of environmental crafting, where individuals add a sense of coherence by improving the workplace environment, that is, by minimising demands and increasing resources.…”
Section: Theoretical Implicationsmentioning
confidence: 92%
“…Consequently, there is imperative to investigate a broader array of WE determinants to deepen the understanding of this construct [ 6 ]. While numerous studies have explored the nexus between trust and motivational outcomes organizational citizenship behavior, job satisfaction, and turnover intentions [ 25 ], the relationship between trust and WE remains relatively under-researched. Such observations indicate a potential linkage between trust climate (TC) and WE that remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%